KLARIFIKASI DALAM MENENTUKAN PESERTA PEMILIH UNTUK MEMBANTU PETUGAS PANTARLIH DALAM MENENTUKAN HAK PEMILIH DALM PEMILU 2024 - Widodo, Edy (JURNAL PENGABDIAN MANDIRI, 2023)
In the current digital era, the general public does not yet understand the term digitization, therefore the government, in seeking correct and valid data, collects citizen data according to KTPs and residences manually. Then valid data will later be used as a potential voter in the 2024 PEMILI. Therefore the government formed a committee to record all local residents according to their KTPs and residences called PANTARLIH officers (Voters Data Updating Officers) who are the spearhead of the KPU in updating and registering voters. The data collection includes age, having an ID card, family card, all of this is recorded according to the local address, so that the voters' data will be truly local residents. The results of this data will become valid voter data in the 2024 election era.